MUATAN NAQSYABANDIYAH DALAM KITAB QURRAH AL- AṢFIYĀ’ KARYA KIAI ZAINULLAH MALANG: SEBUAH PENYELIDIKAN INTERTEKSTUAL - Muhammad Hilal (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2023)
Qurrah al-Aṣfiyā’ ‘alā Sharḥ Hidāyah al-Adhkiyā’ is a book written by Kiai Zainullah from Malang. The book explains the teachings and daily practices of sufism. However, the writer seems to have inserted some distinctive messages of the Naqshbandiyya tariqa. Therefore, this article aims to investigate and uncover those Naqshabandi contents. The analytical techniques used here are content analysis and intertextual study. After a deep investigation and analysis, this article concludes that there are three distinctive explanations of Naqshbandiyya tariqa: first, the discussion regarding the first chain of transmission (sanad) and the authority of Naqshbandiyya tariqa; second, the Naqshbandiyya’s chain of transmission, especially in Madura island, which ultimately reaches the author of Qurrah al-Asfiyā; thirdly, the discussion regarding the priority of silent remembrance (dhikr khafī) which is a typical remembrance technique of Naqshbandiyya tariqa.